2020
DOI: 10.37201/req/098.2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of compliance with the antibiotic prophylaxis protocol in hysterectomy. Prospective cohort study

Abstract: Objectives. Health care-related infections are a public health problem, among them surgical site infection (SSI) are the most frequent in hospitals. The objetive of this study was to assess the effect of the compliance to antibiotic prophylaxis protocol on the incidence of surgical site infection in hysterectomized patients. Material and methods. A prospective cohort study was carried out between October 2009 and December 2018. The incidence of SSI was studied after a maximum period of 30 days from the moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
2
1
1
Order By: Relevance
“…The present study found that, of the total number of surgeries, antibiotics were used in 94.5%; however, the indication for antibiotic prophylaxis only corresponded to 38.2%. This is different from what was found by Uppendahl and Gil, who, in their respective studies, found a frequency of use of prophylaxis above 95% [19,20], even lower than that described by Romero, in a Latin American context, where the overall use of antimicrobial prophylaxis was 69.9% [13]. The low adherence to prophylaxis in Peru is notorious.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The present study found that, of the total number of surgeries, antibiotics were used in 94.5%; however, the indication for antibiotic prophylaxis only corresponded to 38.2%. This is different from what was found by Uppendahl and Gil, who, in their respective studies, found a frequency of use of prophylaxis above 95% [19,20], even lower than that described by Romero, in a Latin American context, where the overall use of antimicrobial prophylaxis was 69.9% [13]. The low adherence to prophylaxis in Peru is notorious.…”
Section: Discussioncontrasting
confidence: 77%
“…A study in Israel showed that 95.6% of patients received the correct antibiotic [29]. In contrast, a study in Spain identified the timing of initiation and correct antibiotic selection as the main causes of non-compliance [20]. Importantly, differences in compliance rates could be attributed to the presence of antibiotic optimization and monitoring units in some hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the adequacy of the items of the antibiotic prophylaxis protocols can help controlling SSIs and the antibiotics to be effective, as shows different previous research 35 , 38 , 42 .…”
Section: Discussionmentioning
confidence: 80%
“…Durante el proceso de preparación prequirúrgica de todo paciente que ingresa al servicio de salas de cirugía, uno de los aspectos de mayor relevancia es la administración de profilaxis antibiótica (30) , la cual fue administrada a la totalidad de pacientes de la muestra. Sin embargo, un poco menos de la cuarta parte de los pacientes no recibió el medicamento entre 30 y 60 minutos antes de la incisión quirúrgica, de acuerdo con la recomendación dada en diferentes guías y estudios internacionales (31,32,33) , hallando similitud con lo reportado por Gutiérrez et al (34) , quienes identificaron que en el 12% de los casos se presentó este error, exponiendo al paciente a múltiples riesgos, como generar o exacerbar reacciones adversas propias de cada medicamento y/o interacciones farmacológicas al administrar el antibiótico en bolo y en concomitancia con agentes hipnóticos, sedantes, opioides y relajantes musculares durante la inducción de anestesia, además del riesgo aumentado de desarrollar infección del sitio operatorio al no alcanzar concentraciones óptimas del fármaco en los tejidos antes de ser expuestos a la incisión quirúrgica (34,35,36,37) .…”
Section: Preoperatoriounclassified